2015
DOI: 10.1007/s00508-015-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Moclobemide as add-on therapy to agomelatine in a patient with treatment-resistant major depressive disorder: a psychopharmacological case

Abstract: In this report, we identified a case with positive evidence of this antidepressant combination relieving the symptoms of treatment-resistant MDD, which is otherwise difficult to manage. This case report may serve to help clinicians and clinical pharmacists as a new treatment option for treatment-resistant MDD, although further research is needed to confirm this practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…After moclobemide was added to agomelatine, the patient improved significantly and did not experience any serious side effects. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After moclobemide was added to agomelatine, the patient improved significantly and did not experience any serious side effects. 26…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Recently, several articles were published about patients that had achieved remission of their mental illness after combining agomelatine with standard antidepressants like escitalopram, venlafaxine, and other anti-depressive drugs. [22][23][24][25][26] Conversely, there are publications available on agomelatine combinations with duloxetine that describe the development of serious adverse events. 27,28 In summary, the main therapeutic advantages or disadvantages of agomelatine combinations with other antidepressants, and full texts of published articles found on PubMed were analyzed from a pharmacological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…38 One case report depicted successful remission of TRD by combining moclobemide with agomelatine. 39 Another case report showed the combination of bupropion with agomelatine as a successful strategy for TRD. 40 One RCT involving a 12-week treatment period and a double-blind extension for 12 weeks compared agomelatine and escitalopram for efficacy, subjective sleep and tolerability.…”
Section: Agomelatinementioning
confidence: 99%
“…Stuhec et al [124] identified a case with positive evidence of combination moclobemide and agomelatine relieving the symptoms of treatment-resistant MDD, which is otherwise difficult to manage. This case report may serve to help clinicians and clinical pharmacists as a new treatment option for treatment-resistant MDD, although further research is needed to confirm this practice.…”
Section: Atypical Antidepressantsmentioning
confidence: 99%